2013
DOI: 10.1007/s00402-013-1851-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased post-operative ischemia in the femoral head found by microdialysis by the posterior surgical approach: a randomized clinical trial comparing surgical approaches in hip resurfacing arthroplasty

Abstract: HRA in the posterior approach results in increased post-operative ischemia in the femoral head and neck although during surgery, no difference in the blood flow was found. Still, the antero-lateral approach also causes considerable ischemia and other possible explanations, such as damage to the retinacular vessels during surgery or altered microcirculation because of heating from the cementation process, needs to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…For vertebral cancellous bone, ischemic conditions have not previously been shown. However, these findings are consistent with previous microdialysis results of ischemia in bone demonstrated in the femoral head of both humans and pigs (12)(13)(14). Altogether, the findings from the present study confirms previous findings of ischemia in bone and the intervertebral disc.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…For vertebral cancellous bone, ischemic conditions have not previously been shown. However, these findings are consistent with previous microdialysis results of ischemia in bone demonstrated in the femoral head of both humans and pigs (12)(13)(14). Altogether, the findings from the present study confirms previous findings of ischemia in bone and the intervertebral disc.…”
Section: Discussionsupporting
confidence: 94%
“…Glycerol is liberated as a result of cell membrane damage. As previously demonstrated, the trauma of drilling in bone tissue results in initially elevated glycerol concentrations (12)(13)(14). The lowest mean glycerol concentrations were found in the intervertebral disc, which may be explained by a lower number of cells in this compartment.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Twenty‐one studies were identified using near infrared spectroscopy (NIRS) and 10 studies were identified using photoplethysmography (PPG) non‐invasively on in vivo bone tissue . Fifty‐seven studies were identified using laser Doppler flowmetry (LDF) in vivo of which 56 were intra‐operative. Only one study using LDF attempted to measure bone non‐invasively .…”
Section: Resultsmentioning
confidence: 99%